2018
DOI: 10.5387/fms.2018-14
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided fine needle aspiration for pancreatic cancer

Abstract: Since the development of endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) in the early 1990s, its application has been extended to various diseases. For pancreatic cancer (PC), EUS-FNA can obtain specimens from the tumor itself with fewer complications than other methods. EUS-FNA can also be more useful for TNM staging than other imaging modalities. Furthermore, EUS-FNA can contribute to precision medicine by obtaining tissue for immunohistochemical or genetic studies from primary or metastatic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Hewitt et al (21) performed a meta-analysis of 4984 patients and demonstrated a pooled sensitivity of 0.85 and a specificity of 0.98 for malignant cytology. Reports have shown that the accuracies of T-staging by EUS range from 62-94%, and those of N-staging range from 50-86% (22). Although EUS-FNA provides a valuable means for pancreatic cancer diagnosis, it shows a poor staging performance, and it is invasive and limited to the detection location of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Hewitt et al (21) performed a meta-analysis of 4984 patients and demonstrated a pooled sensitivity of 0.85 and a specificity of 0.98 for malignant cytology. Reports have shown that the accuracies of T-staging by EUS range from 62-94%, and those of N-staging range from 50-86% (22). Although EUS-FNA provides a valuable means for pancreatic cancer diagnosis, it shows a poor staging performance, and it is invasive and limited to the detection location of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, EUS-FNA has been widely applied to diagnose lesions in the digestive tract and nearby areas. This diagnostic technique is suitable for diagnosing submucosal tumors in the digestive tract ( 2 ), and space-occupying lesions in the lymph nodes ( 3 ), mediastinum ( 4 , 5 ), pancreas ( 6 , 7 ), liver ( 8 ), and adrenal glands ( 9 , 10 ). The clinical value of EUS-FNA for diagnosing space-occupying lesions in these organs has been widely acknowledged.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic cancer is a highly aggressive tumor with a poor prognosis (1). Its mortality almost equals incidence and the 5-year survival rate is only 6% (2). The low survival rate is due to the late presentation of symptoms, which often results in a delayed diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of endoscopic ultrasonography (EUS) and EUS-guided fine needle aspiration (EUS-FNA) has provided an important diagnostic method for various visceral malignancies, especially pancreatic lesions (4)(5)(6). EUS-FNA can provide real-time and direct visualization of structures within or outside the gastrointestinal lumen and can obtain an adequate sample, which is critical for precise diagnosis and management (2,7). A recent metaanalysis of randomized controlled trials revealed that the sensitivity of EUS-FNA is about 85-93% (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation